Number one Chinese restaurant [large type] : a novel - Li, Lillian (Thorndike Press, a part of Gale, a Cengage Company, 2018)
"The Beijing Duck House in Rockville, Maryland, is not only a beloved go-to setting for meals and celebrations; it is its own world, inhabited by waiters and staff who have been fighting, loving, and aging within its walls for decades. But when disaster strikes, this working family's controlled chaos is set loose. Generous in spirit, unaffected in its intelligence, multi-voiced, poignant, and darkly funny, Number One Chinese Restaurant is an unforgettable story about the ways that our families destroy us while also keeping us grounded and alive."--Back cover.